Detection of Rickettsia amblyommatis and Ehrlichia chaffeensis in Amblyomma americanum Inhabiting Two Urban Parks in Oklahoma - Small, Mariah (Vector Borne Zoonotic Dis, 2021)
For the past 30 years, the number of people infected with causative agents of ehrlichiosis, Rocky Mountain spotted fever, and spotted fever group rickettiosis (SFGR) has increased in Oklahoma. However, there is a lack of data on pathogen prevalence within urban environments. To assess the prevalence of tick-borne pathogens in different environments, 434 Amblyomma americanum (lone star) ticks were collected from the environment in two parks in Edmond, Oklahoma. The presence of Ehrlichia spp. and spotted fever group (SFG) Rickettsia spp. was determined using quantitative real-time polymerase chain reaction (qPCR). 33.6% (146/434) of the A. americanum ticks were positive for Rickettsia amblyommatis and 15.2% (66/434) were positive for Ehrlichia chaffeensis. No ticks were positive for other SFG Rickettsiae (R. rickettsii, R. parkeri) or other Ehrlichiae (E. ewingii, and Panola Mountain Ehrlichia). These studies provide increased understanding of the potential risk for encountering tick-borne pathogens in urban environments.